EXPLORING WRITING PRACTICES IN EFL CLASSROOM: A CASE STUDY AT ENGLISH DEPARTMENT IAIN SYEKH NURJATI CIREBON - Astri Rahayu; Farouk Imam Arrasyid (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2016)
Abstract: This article investigated the type of literacy writing practices in teaching writing for communication in EFL classroom especially in making descriptive text and the teacher’s ways used in the writing process. This article reports on a descriptive qualitative exploration. This article aimed to find out the types of literacy writing practices are found in EFL class room and to identify how the teacher use the available materials in writing practices EFL classroom. This article uses three techniques in collecting data: observation, Interview and study of document. This study shows that the lecturer of EFL learner’s uses variety approaches, methods, strategies and techniques when the researcher recorded teaching and learning writing process using field notes observation. There are use five processes: pre writing stage, writing stage, revising, editing and publishing. Several variety approaches (e.g. student center, genre based and process oriented). Then, method is mind mapping. Besides that, there are strategies (e.g. Brainstorming, guided writing, and collaborative strategy. There are techniques used include scaffolding, listing, free writing and clustering. It can help enhancing the students’ proficiency in literacy practices. Beside that the comprehension in order to create teaching and learning becomes effective and efficient in EFL classroom.     Key words: Literacy, Writing Practices, EFL, Classroom.